Lgt Processing Is an Essential Step in Streptococcus suis Lipoprotein Mediated Innate Immune Activation - Wichgers Schreur, P.J.; Rebel, J.M.J.; Smits, M.A.; van Putten, J.P.M.; Smith, H.E. (Public Library of Science, 2011)
Background: Streptococcus suis causes invasive infections in pigs and occasionally in humans. The host innate immune system plays a major role in counteracting S. suis infections. The main components of S. suis able to activate the innate immune system likely include cell wall constituents that may be released during growth or after cell wall integrity loss, however characterization of these components is still limited. Methology/Principal Findings: A concentrated very potent innate immunity activating supernatant of penicillin-treated S. suis was SDS-PAGE fractionated and tested for porcine peripheral blood mononucleated cell (PBMC) stimulating activity using cytokine gene transcript analysis. More than half of the 24 tested fractions increased IL-1b and IL-8 cytokine gene transcript levels in porcine PBMCs. Mass spectrometry of the active fractions indicated 24 proteins including 9 lipoproteins. Genetic inactivation of a putative prolipoprotein diacylglyceryl transferase (Lgt) gene resulted in deficient lipoprotein synthesis as evidenced by palmitate labeling. The Lgt mutant showed strongly reduced activation of porcine PBMCs, indicating that lipoproteins are dominant porcine PBMC activating molecules of S. suis. Conclusion/Significance: This study for the first time identifies and characterizes lipoproteins of S. suis as major activators of the innate immune system of the pig. In addition, we provide evidence that Lgt processing of lipoproteins is required for lipoprotein mediated innate immune activation.